2021
DOI: 10.3390/ma14092438
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cathodic Protection on Reinforced Concrete with Fly Ash Using Electrochemical Noise

Abstract: Corrosion of steel reinforcement is the major factor that limits the durability and serviceability performance of reinforced concrete structures. Impressed current cathodic protection (ICCP) is a widely used method to protect steel reinforcements against corrosion. This research aimed to study the effect of cathodic protection on reinforced concrete with fly ash using electrochemical noise (EN). Two types of reinforced concrete mixtures were manufactured; 100% Ordinary Portland Cement (OCP) and replacing 15% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Recently published work by Garcia-Contreras et al [ 8 ] and Permeh et al [ 9 ] has used ENM techniques to monitor pitting corrosion in post-tensioned bridges and study the effect of fly ash additions on reinforcement subjected to cathodic protection, respectively. A review of electrochemical noise carried out in 2020 by Da-Hai Xia et al [ 10 ] identified the numerous experimental arrangements and models that have been employed in an attempt to achieve near-quantitative evaluation of corrosion rates for a range of environments, including steel in concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Recently published work by Garcia-Contreras et al [ 8 ] and Permeh et al [ 9 ] has used ENM techniques to monitor pitting corrosion in post-tensioned bridges and study the effect of fly ash additions on reinforcement subjected to cathodic protection, respectively. A review of electrochemical noise carried out in 2020 by Da-Hai Xia et al [ 10 ] identified the numerous experimental arrangements and models that have been employed in an attempt to achieve near-quantitative evaluation of corrosion rates for a range of environments, including steel in concrete.…”
Section: Introductionmentioning
confidence: 99%
“…It was evidenced that the phosphating treatment of fibers allows to enhance the bond strength between steel and concrete and improves the corrosion resistance of fibers without affecting their surface morphology. Finally, the paper by Garcia-Contreras et al [ 14 ] studied the effect of impressed current cathodic protection on reinforced concrete manufactured with fly ash as cement replacement. Results evidenced that the microstructure of cementitious matrix strongly influenced the corrosion behavior of steel in concrete.…”
mentioning
confidence: 99%